A look at the actual cost of capital of US firms - David J. Moore (Cogent Economics & Finance, 2016)
The capital asset pricing model (CAPM) receives both criticism and widespread adoption by practitioners and academics as the weighted average cost of capital (WACC) equity component. This study introduces two new costs of equity measures to address CAPM criticisms and provide new perspective on WACC estimates. The firm-based measure focuses on firm-investor cash flows while the market-based measure focuses solely on actual market returns. This study applies its firm and market-based WACC measures, along with the traditional CAPM-based WACC measure, to a broad sector-based cross section from 1972 to 2015. Results show that traditional CAPM-based WACC estimates consistently lie between the new firm and market-based WACC estimates. The central positioning of CAPM WACC supports its use as a conservative hurdle rate estimate for firms and a conservative expected return estimate for investors relative to actual returns.
Keywords: G11; G12; G31; G32; G35; C22; 330; cost of capital; WACC; CAPM; return; industry